Feasibility and efficacy of a nurse practitioner-and pharmacist-led hypertension clinic. Issue 9 (29th September 2022) - Speed, Shelley; Schneider, Nathan; Stutzman, Sonja E.; Olson, DaiWai M.; Higbea, Ashley
ABSTRACT: Hypertension (HTN) affects over one third of adults in the United States. Blood pressure (BP) management and patient education are provided by physicians, advanced practice clinicians, pharmacists, and nurses. In the traditional medical/clinic model, physicians have provided and directed HTN care. However, advanced practice nurses and pharmacists are also well trained and positioned to manage HTN. The purpose of this study was to explore the feasibility of an HTN clinic, led by a nurse practitioner (NP) and PharmD, specifically analyzing if targeted HTN can be achieved in this setting. Registry data were used to analyze the initial and the most recent visit BP levels in patients who were seen in an NP/PharmD-led HTN clinic. Measures of central tendency and differences between initial and most recent visit were also compared. A total of 46 patients were included in this analysis. Data showed that there was no statistically significant difference in the first visit (144/86) and the most recent visit (138/84) BP ( p = .26), but that there was a clinical trend in decreasing BP as well as narrowing of BP ranges and interquartile ranges between visit. The NP/PharmD-led clinic is feasible and can help lower BP and narrow ranges toward targeted BP.